Style rozwiązywania konfliktów przez młodzież gimnazjalną = Ways of resolving conflicts by middle school students - Miłkowska, Grażyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
One of the causes of behavior disorders of young people is the inability to cope with conflict situations. Teenagers` disagreements with others are of a particularly turbulent nature, caused by the specificity of adolescence as well as new developmental tasks and social roles.
Keywords: młodzież gimnazjalna; konflikt; zaburzenia zachowania; rozwiązywanie konfliktów; Zielona Góra